Penerapan metode pembelajaran guided note taking untuk meningkatkan hasil belajar bahasa Indonesia peserta didik di sekolah dasar - Devina Nazywa Asis Asis; Sukmawaty Sukmawaty; Mirnawati Mirnawati (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
This study aims to determine the implementation of the guided note taking (GNT) method in improving the Indonesian language learning outcomes of fourt-grade students at SDN 228 Lagaroang. This is a Classroom action research (CAR) conducted in two cycles using a qualitative approach. The research subjects we're 28 students, consisting of 14 boys and 14 girls. The GNT method was implemented by providing handouts containing key points with blanks that students we're required to fill during the lesson. The results showed a significant improvement in student learning outcomes Adn Classroom activity. Int he first cycle, the average student score was 64,28% (categorized as good), and in the second cycle, it increased to 92,50% (categorized as very good) . Both teacher and student Activities also improved from good. The implementation of the GNT method proved effective in enchaning student concentration, engagemeng, and understanding of Indonesian language material. Therefore GNT can be considered an innovative and enjoy able teaching strategy to improve student achievement in primary schools.